Activity-based costing (ABC) Model for Public Higher Education Institutions (PHEI) : A guide for a Model development (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The purpose of this study is to develop the Activity-based costing (ABC) model for Bachelor of Accountancy (BACC) program in University of Excellence (UoE) Malaysia. A case study approach using the professional software, ABM-SAS, and the actual expenses figure for BACC for the year 20XX were used to develop the ABC model in this study. The finding showed that the cost computed using the ABC Model is lower as compared to the cost from the traditional (current) method, i.e. RM 8,678.54 and RM 10,509.99, respectively.  The differences amounted RM 1,830.55 in cost calculated by these two systems is not surprising. It is expected as many other researchers have discovered the same pattern on the lower cost of ABC as compared to the traditional method due to several reasons. Among others are,  (i) the inability of the traditional costing system in spreading their costs over larger numbers of students, ii) the support services do not benefit the programmes uniformly and, iii) there were internal cross-subsidies among departments and seriously distorted if support costs were allocated based on head counts. As such, this study confirmed the ability of ABC to act in higher education institutions with the same functions as its functions in the profit and manufacturing setting.